Cancer stem cells: Road to therapeutic resistance and strategies to overcome resistance - Makena, Monish Ram; Ranjan, Alok; Thirumala, Vani; Reddy, Arubala P (Biochimica et biophysica acta. Molecular basis of disease, 2020)
Unlike other normal cells, a subpopulation of cells often termed as “stem cells” are long-lived and generate cellular progeny throughout life. Cancer stem cells (CSCs) are rare immortal cells within a tumor that can both self-renew by dividing and giving rise to many cell types that constitute the tumor. CSCs also have been shown to be involved in fundamental processes of cell proliferation and metastatic dissemination. CSCs are generally resistant to chemotherapy and radiotherapy, a subset of remaining CSCs after therapy can survive and promote cancer relapse and resistance to therapies. Understanding the biological characteristics of CSCs, the pathways leading to their sustainability and proliferation, and the CSCs role in drug resistance is crucial for establishing novel tumor diagnostic and therapeutic strategies. In this review, we address the pathways that regulate CSCs, the role of CSCs in the resistance to therapy, and strategies to overcome therapeutic resistance. •Cancer stem cells (CSCs) promote cancer relapse and resistance to therapies.•CSCs cause drug resistance by regulating many cellular functions.•Targeting pathways deregulated in CSCs could be a strategy to treat relapse cancers.•Combination of conventional and novel treatments could overcome CSC resistance.